Core histones govern echinocandin susceptibility in Candida glabrata - Aditi Pareek; Rupinder Kaur (Microbiology Spectrum)
ABSTRACT The dynamic chromatin structure regulates many biological processes including gene expression, DNA repair, and genome stability in eukaryotic cells. However, its role in governing antifungal drug susceptibility in medically important fungi is just beginning to be deciphered. Chromatin architecture is maintained by a complex interplay among histone protein stoichiometry sustainment, post-translational modifications of histone proteins, and the activity of chromatin remodeling complexes. Herein, we report that the reduced gene dosage of histone core proteins in the opportunistic human fungal pathogen Candida glabrata leads to increased susceptibility toward the widely used, cell wall-targeting echinocandin antifungal drugs. Our comprehensive characterization of single and double histone mutants revealed that linker histone H1 loss had no effect on cell physiology and drug susceptibility, whereas low H2A, H2B, H3, and H4 protein levels resulted in decreased reactive oxygen species production, altered biofilm production, elevated DNA damage, and echinocandin stress susceptibility. Importantly, not all core histone mutants exhibited an increased sensitivity to other cell wall stressors, thereby precluding a general cell wall defect accounting solely for the increased caspofungin susceptibility. Finally, we show that the histone H3 acetylation at lysine-56 may be pivotal to caspofungin response of C. glabrata, as H3K56Ac levels were reduced in both core histone mutants and upon caspofungin exposure, with H3K56 acetyltransferase (CgRtt109)- and nucleosome assembly factor (CgAsf1)-lacking mutants displaying increased caspofungin susceptibility. Besides demonstrating the histone requirement for the survival of C. glabrata in the mouse systemic candidiasis model, our findings unveil histone dosage-regulated cellular processes that impact echinocandin susceptibility.IMPORTANCEEchinocandin antifungals, which impede cell wall synthesis, are often used to treat Candida bloodstream infections. The human opportunistic fungal pathogen Candida (Nakaseomyces) glabrata is increasingly being reported to exhibit co-resistance to echinocandins and ergosterol biosynthesis-inhibitory azole drugs in hospitals worldwide. However, the role of histones, protein-building blocks of the nucleosome, in governing echinocandin resistance in C. glabrata is not understood. Herein, we show that the reduced gene dosage of core histone proteins, but not of the linker histone, leads to echinocandin susceptibility, which is partly due to increased ROS levels. Additionally, our data implicate histone H3 acetylation at lysine-56 in the caspofungin response of C. glabrata. Since the emerging echinocandin resistance is an impediment to successful antifungal therapy, our findings open up a new research avenue of pharmacological targeting of histone proteins that could potentially block echinocandin resistance and attenuate C. glabrata survival in the host.